Rengalin, a New Efficacious and Safe Antitussive Agent. Results of a Randomized, Comparative, Multicenter Clinical Trial in Patients with Acute Respiratory Tract Infections - A. L. Akopov; E. B. Aleksandrova; M. M. Il'kovich; D. V. Petrov; V. I. Trofimov (Антибиотики и Химиотерапия, 2020)
Rengalin is a release-active combination antitussive drug based on antibodies to bradykinin, to histamine and morphine. It acts at various mechanisms of cough reflex by modifying endogenous target molecules and their interaction with receptors. The drug's efficacy, as demonstrated previously in experimental and clinical studies, is mediated by specific release-activity obtained as a result of the production process. Methods. Efficacy and safety assessment of rengalin in the treatment of cough induced by acute upper respiratory tract infections (URIs) in comparison with a complex codeine-containing drug (codelac®) was performed as part of a multicenter, randomized clinical trial involving 143 patients. All the participants presented with dry/non-productive cough caused by URIs (pharyngitis, laryngitis, tracheitis, tracheobronchitis, bronchitis). The duration of cough varied between 12 hours and 7 days. Rengalin was administered in 73 patients receiving 2 tablets 3 times daily for initial three days, and half reduced doses - for the subsequent four days; codelac® was administered in 70 patients who were given 1 tablet 3 times daily for the entire treatment period (7 days). Primary efficacy endpoints were time to cough resolution and reduction in the severity of the cough (scored using a Cough Severity Scale). One patient in Rengalin group and three patients in Codelac group were withdrawn from the study. The article presents treatment outcomes obtained for 139 participants who completed the study in accordance with the protocol (Per Protokol-analysis). The data analysis was based on a non-inferiority (or comparability) statistical design for efficacy endpoints. Results. The antitussive effect of rengalin was significantly comparable (р